Work less but stay longer: Mature worker response to a flexibility reform - Erik Hernæs; Zhiyang Jia; John Piggott; Trond C. Vigtel (Statistics Norway, Research Department, 2020)
Reducing the eligibility age for pension benefits is considered by many as a policy that will discourage labor supply by mature workers. This paper analyzes a recent Norwegian pension reform which effectively lowered the eligibility age of retirement from 67 to 62 for a group of workers. For the individuals we study, the expected present value of benefits was held constant by introducing flexible claiming and actuarially adjusting the periodic pension payment. This provides us with a unique opportunity to study the isolated impact of increased flexibility. As expected, we find that on average workers reduced their earnings and working hours. However, this initial negative effect is partially offset by an increase in labor force participation rate later at age 64 and 65. Our findings suggest that increased flexibility could potentially serve as a policy aimed at increasing the labor supply of older workers through promoting gradual exit from the labor force.
Keywords: J14; J23; J26; 330; Retirement; Pension; Flexibility